2019
DOI: 10.1108/jarhe-05-2019-0105
|View full text |Cite
|
Sign up to set email alerts
|

Examining the impact of case-based learning on student engagement, learning motivation and learning performance among university students

Abstract: Purpose The purpose of this paper is to examine the impact of case study-based learning on student’s engagement, learning motivation and learning performance among university students of Pakistan. Design/methodology/approach The research model is analyzed with structural equation modeling. The analysis is done with the application of the measurement model and the structural model. Findings The findings revealed that case study-based learning enhances student engagement, and a significant and positive relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 38 publications
2
31
0
11
Order By: Relevance
“…On the other hand, if feedback suggests surface understanding, such as rote learning or replication of any task they have done, then the student may not put any further effort into learning material (Carless, 2015;Raza et al, 2020b). In the same vein, Nichols and Dawson (2012) and Raza et al (2019) discussed the requirements of assessment, including feedback and determined student's motivation and engagement in learning activities. The study further argued that the judgments of analytical skills motivate the student to study the concepts carefully.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, if feedback suggests surface understanding, such as rote learning or replication of any task they have done, then the student may not put any further effort into learning material (Carless, 2015;Raza et al, 2020b). In the same vein, Nichols and Dawson (2012) and Raza et al (2019) discussed the requirements of assessment, including feedback and determined student's motivation and engagement in learning activities. The study further argued that the judgments of analytical skills motivate the student to study the concepts carefully.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the present research consists of 431 respondents. The sample size selected for the data was based on the guidelines presented by Comrey and Lee (2013) and Raza et al (2019) that the sample of 50 is considered as inferior, 300 as good, 500 as very good and 1,000 was regarded as an excellent sample concerning factor analysis.…”
Section: Methodsmentioning
confidence: 99%
“…When students work independently on a case, then analytical skills can be improved, while in a group setting, critical thinking skills through participation in discussions can be enhanced (Tan, 2019). It can be concluded that case-based learning is an effective teaching method that enhances learning motivation and where this is combined with cooperative learning, a range of skills can be developed (Raza, Qazi and Umer, 2020).…”
Section: Case Study Approachmentioning
confidence: 99%